The Role of Business Analysis Capability in Enhancing Organizational Agility and Performance: The Mediating Effect of Information Quality and Innovation Capability in the Manufacturing Industry in Batam City - Antony Sentoso; William Vanders Phang; Alden Nelson (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the role of business analysis capability in improving organizational agility and performance in manufacturing industry in Batam City, by considering information quality and innovation capability as mediating variables. Using descriptive quantitative approach, data were obtained from 274 respondents through questionnaires and analyzed using Smart PLS. The results showed that business analysis capability has a significant influence on information quality and innovation capability, which in turn improve organizational agility. Organizational agility is shown to contribute positively to organizational performance, especially in responding to market changes quickly and efficiently. This research confirms the importance of developing business analysis capabilities integrated with information technology and strategic innovation to support the competitiveness of the manufacturing industry in the midst of global market dynamics.